Low-temperature, high-efficiency and high-adaptability chromium-indium-based composite oxide denitration catalyst as well as preparation method and application thereof
By using chromium indium-based composite oxide as a denitrification catalyst, combining the oxidation capacity of manganese oxide and the acidic sites of chromium and indium species, the problems of low-temperature NOx removal and HCl poisoning were solved, and efficient and highly adaptable denitrification effect was achieved.
Patent Information
- Application Number
- CN202510024654.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The prior art is difficult to efficiently remove NOx in the flue gas of industrial boilers under low temperature conditions, and there is a problem of insufficient anti-HCl poisoning ability, which limits the adaptability of denitrification catalysts.
The chromium indium-based composite oxide is used as the denitrification catalyst to enhance the oxidation capacity through manganese oxide, and the acidic sites of Cr-OH and In-OH are formed through chromium and indium species, reducing the adsorption capacity of HCl and enhancing the catalyst's anti-HCl poisoning ability.
In the temperature range of 150-325°C, the NOx conversion rate is higher than 80%, and good denitrification activity is maintained in the presence of HCl, which significantly improves the low temperature, high efficiency and high adaptability of the catalyst.
Smart Images

Figure CN119701934A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of denitration catalysts, and in particular to a low-temperature, high-efficiency and high-adaptability chromium-indium-based composite oxide denitration catalyst, and a preparation method and application thereof. Background Art
[0002] Industrial boiler flue gas emissions have the characteristics of low flue gas temperature and complex pollutant composition. The flue gas temperature of industrial boilers is lower than 250℃, or even lower than 200℃. Traditional commercial ammonia selective catalytic reduction denitrification catalyst V 2 O 5 -WO 3 / TiO 2 , usually operating at around 350°C, which is difficult to meet the requirements of industrial boiler flue gas under complex working conditions. In addition, the pollutants in industrial boiler flue gas are complex, in addition to containing a large amount of nitrogen oxides (NO x ), and acidic substances such as HCl, which poison and deactivate the catalyst, which poses a challenge to the adaptability of the catalyst to complex working conditions. The above problems have become an important bottleneck restricting the development of low-temperature, high-efficiency and high-adaptability denitrification catalysts.
[0003] Surface oxidation regulation is an effective means to improve the low-temperature activity of denitrification catalysts. For example, adding metal oxides such as manganese, iron, and cerium to enhance oxidation ability promotes the adsorption and activation of ammonia molecules, thereby reducing the activation temperature of the catalyst. However, excessive oxidation ability leads to N 2 O byproducts are formed, so how to obtain moderate oxidation capacity is one of the difficulties in designing low-temperature denitrification catalysts. On the other hand, HCl acidic substances in flue gas are easy to combine with the active centers of catalysts (such as Lewis acid centers), causing catalyst poisoning and decreased activity. Therefore, reducing the stability of HCl adsorbed species and protecting active centers is another difficulty in designing highly adaptable catalysts. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitrification catalyst and its preparation method and application, which can reduce NO x The conversion rate is higher than 80%. At the same time, the catalyst has the ability to resist HCl poisoning and can still maintain good denitrification activity at low temperatures in the presence of HCl.
[0005] The technical solution of the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing a low-temperature, high-efficiency, and highly adaptable chromium-indium-based composite oxide denitrification catalyst, comprising the following steps:
[0007] S1: adding tetrabutyl titanate to anhydrous ethanol, mixing, and continuously stirring to form solution A; mixing manganese nitrate solution with anhydrous ethanol to form solution B; dropping solution B into solution A, continuously stirring to form a gel, and placing at room temperature for aging;
[0008] S2 drying the aged gel and then calcining it, and taking it out after naturally cooling to room temperature to obtain a manganese-modified titanium dioxide carrier powder;
[0009] S3: adding manganese-modified titanium dioxide carrier powder into water, stirring continuously to form a uniform turbid liquid, adding polyvinyl pyrrolidone (PVP), stirring until completely dissolved, adding chromium nitrate and indium nitrate in sequence, stirring until completely dissolved, then adding hexamethylenetetramine and ethylene glycol, stirring continuously in a water bath heating environment until the mixed turbid liquid changes color;
[0010] S4: further evaporate and dehydrate the mixed turbid liquid after discoloration to obtain a gel, dry the gel and then calcine it, and then take it out after naturally cooling to room temperature to obtain a chromium-indium-based composite oxide denitrification catalyst.
[0011] Preferably, in step S1, the concentration of manganese nitrate solution is 50-55wt.%, the volume ratio of tetrabutyl titanate to anhydrous ethanol is (0.5-0.6):1, the volume ratio of manganese nitrate solution to anhydrous ethanol is (0.2-0.4):1, the second continuous stirring time is 3-5h, and the aging time is 22-24h.
[0012] Preferably, in step S2, the gel drying temperature is 70-80°C, and the drying time is 10-12h; during calcination, the heating rate is 4.5-5.5°C / min, the calcination temperature is 450-500°C, and the calcination time is 4-5h.
[0013] Preferably, in step S3, the content of manganese-modified titanium dioxide carrier powder in the uniform turbid liquid is 10-11wt.%, the water bath heating temperature is 75-80°C, the molar ratio of polyvinyl pyrrolidone, hexamethylenetetramine, ethylene glycol, and chromium-indium metal ions in chromium nitrate and indium nitrate is (40-42):(98-102):(48-50):1; and the stirring time of the final mixed turbid liquid is 5-6h.
[0014] Preferably, in step S4, the evaporation dehydration temperature is 75-80°C.
[0015] Preferably, in step S4, the gel drying temperature is 90-100°C, and the drying time is 10-12h; during calcination, the heating rate is 4.5-5.5°C / min, the calcination temperature is 550-600°C, and the calcination time is 4-5h.
[0016] Preferably, in the chromium-indium-based composite oxide denitration catalyst, the manganese content is 4-4.5wt.%, the chromium content is 0.9-1wt.%, and the indium content is 1.8-2wt.%.
[0017] In a second aspect, the present invention provides a low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst prepared by the preparation method of the above-mentioned low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst.
[0018] In a third aspect, the present invention provides the use of the above-mentioned low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitrification catalyst, wherein the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitrification catalyst removes NO x When, the reaction temperature is 150-325°C.
[0019] In the present invention, manganese oxide serves as the main oxidation active site, which can promote the activation of adsorbed ammonia species to form -NH 2 Intermediate species, reduce the reaction energy barrier of SCR reaction, thereby improving the low-temperature SCR denitration performance of denitration catalyst. At the same time, chromium and indium species form Cr-OH and In-OH, providing abundant Bronsted acid sites for the catalyst, which is conducive to the adsorption of ammonia molecules, further providing ammonia source for subsequent manganese oxidation, and accelerating the reaction; on the other hand, the Bronsted acid sites provided by chromium and indium species can provide hydrogen protons, inhibiting the deep poisoning and inactivation of HCl after HCl adsorption and combining with surface metal ions to form chloride salts, thereby enhancing the anti-HCl poisoning ability of denitration catalyst.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention uses manganese to modify TiO 2 Improve the oxidation capacity of the denitrification catalyst and avoid excessive oxidation of NH by forming manganese oxide crystals 3 Formation of N 2 O; Application of Cr and In species coated on Mn-modified TiO 2 The surface of the catalyst creates an acidic environment (Cr-OH and In-OH), thereby reducing the HCl adsorption capacity and improving the adaptability of the denitrification catalyst. 2 O 5 -WO 3 / TiO 2 Compared with the catalyst, the chromium-indium-based composite oxide denitrification catalyst prepared by the present invention can achieve NO x Highly efficient catalytic reduction to form N 2 and H 2 O, in the temperature range of 150-325℃, NO xThe conversion rate is higher than 80%. At the same time, the catalyst has the ability to resist HCl poisoning. After HCl poisoning treatment, the catalyst can react with NO at 175°C. x The conversion rate is higher than 90%, that is, in the presence of HCl, it can still maintain good denitration activity at low temperatures. The denitration catalyst of the present invention can be applied to NO in industrial boilers with complex emission scenarios containing acidic gases. x Selective catalytic reduction, catalytic activity meets emission requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 3 is a graph showing the change in the activity of the denitration catalysts of Examples 1-3 of the present invention with aging time.
[0023] Figure 2 It is a test chart for evaluating the activity of the denitration catalysts of Example 1 of the present invention and Comparative Examples 1-5.
[0024] Figure 3 It is a test chart for evaluating the activity of the denitration catalysts of Example 1 of the present invention and Comparative Examples 6-8.
[0025] Figure 4 This is a test chart for evaluating the adaptability of the denitration catalyst to HCl poisoning in Experimental Example 1-2 of the present invention. DETAILED DESCRIPTION
[0026] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0027] Example 1
[0028] The low-temperature, high-efficiency, and high-adaptability chromium-indium-based composite oxide denitrification catalyst (CrIn / Mn-TiO 2 ) comprises the following steps:
[0029] S1: adding tetrabutyl titanate to anhydrous ethanol at a volume ratio of 0.5:1, and stirring continuously to form solution A; mixing manganese nitrate solution (manganese nitrate solution concentration of 50wt.%) with anhydrous ethanol at a volume ratio of 0.2:1 to form solution B; dropping solution B into solution A, stirring continuously for 3 hours to form a gel, and aging the gel at room temperature for 23 hours;
[0030] S2: The aged gel was transferred to a 70°C drying oven for 12 hours, and then transferred to a muffle furnace for calcination. The heating rate was set to 5°C / min, and the gel was calcined at 500°C for 4 hours. After cooling naturally to room temperature, the gel was taken out to obtain a manganese-modified titanium dioxide carrier powder.
[0031] S3: adding manganese-modified titanium dioxide carrier powder to deionized water and continuously stirring to form a uniform turbid liquid, wherein the manganese-modified titanium dioxide carrier powder content is 10wt.%; adding polyvinyl pyrrolidone to the uniform turbid liquid according to the molar ratio of polyvinyl pyrrolidone, hexamethylenetetramine, ethylene glycol, and metal ions being 40:100:50:1, stirring until completely dissolved, then adding chromium nitrate and indium nitrate, stirring until completely dissolved, and finally adding hexamethylenetetramine and ethylene glycol, stirring continuously for 5 hours in an 80°C water bath environment until the mixed turbid liquid changes color;
[0032] S4 further evaporates and dehydrates the mixed turbid liquid after discoloration in a water bath at 80°C to obtain a gel, which is then dried in air at 100°C for 12 hours and then transferred to a muffle furnace for calcination at 600°C for 4 hours at a heating rate of 5°C / min; after cooling naturally to room temperature, the mixture is taken out to obtain CrIn / Mn-TiO 2 Denitration catalyst, the obtained denitration catalyst has a manganese content of 4wt.%, a chromium content of 1wt.%, and an indium content of 2wt.%.
[0033] Example 2
[0034] The low-temperature, high-efficiency, and high-adaptability chromium-indium-based composite oxide denitrification catalyst (CrIn / Mn-TiO 2 ) comprises the following steps:
[0035] S1: adding tetrabutyl titanate to anhydrous ethanol at a volume ratio of 0.5:1, and stirring continuously to form solution A; mixing manganese nitrate solution (manganese nitrate solution concentration of 54wt.%) with anhydrous ethanol at a volume ratio of 0.3:1 to form solution B; dropping solution B into solution A, stirring continuously for 4 hours to form a gel, and aging the gel at room temperature for 22 hours;
[0036] S2: The aged gel was transferred to a 75°C drying oven for 11 hours, and then transferred to a muffle furnace for calcination. The heating rate was set to 5.5°C / min, and the calcination was performed at 450°C for 5 hours. After cooling naturally to room temperature, the gel was taken out to obtain a manganese-modified titanium dioxide carrier powder.
[0037] S3: adding manganese-modified titanium dioxide carrier powder to deionized water and continuously stirring to form a uniform turbid liquid, wherein the manganese-modified titanium dioxide carrier powder content is 10.5wt.%; adding polyvinyl pyrrolidone to the uniform turbid liquid according to the molar ratio of polyvinyl pyrrolidone, hexamethylenetetramine, ethylene glycol, and metal ions being 41:98:48:1, stirring until completely dissolved, then adding chromium nitrate and indium nitrate, stirring until completely dissolved, and finally adding hexamethylenetetramine and ethylene glycol, stirring continuously for 5.5h in a 78°C water bath environment until the mixed turbid liquid changes color;
[0038] S4 The mixed turbid liquid after discoloration was further evaporated and dehydrated in a 78℃ water bath environment to obtain a gel, which was then dried in air at 95℃ for 11h and then transferred to a muffle furnace for calcination at 580℃ for 4.5h with a heating rate of 4.5℃ / min; after cooling naturally to room temperature, it was taken out to obtain CrIn / Mn-TiO 2 DeNOx catalyst, the obtained deNOx catalyst has a manganese content of 4.2wt.%, a chromium content of 0.95wt.%, and an indium content of 1.9wt.%.
[0039] Example 3
[0040] The low-temperature, high-efficiency, and high-adaptability chromium-indium-based composite oxide denitrification catalyst (CrIn / Mn-TiO 2 ) comprises the following steps:
[0041] S1: adding tetrabutyl titanate to anhydrous ethanol at a volume ratio of 0.6:1, and stirring continuously to form solution A; mixing manganese nitrate solution (manganese nitrate solution concentration of 55wt.%) with anhydrous ethanol at a volume ratio of 0.4:1 to form solution B; dropping solution B into solution A, stirring continuously for 5 hours to form a gel, and aging the gel at room temperature for 24 hours;
[0042] S2: The aged gel was transferred to a drying oven at 80°C for 10 hours, and then transferred to a muffle furnace for calcination. The heating rate was set to 4.5°C / min, and the gel was calcined at 480°C for 4.5 hours. After cooling naturally to room temperature, the gel was taken out to obtain a manganese-modified titanium dioxide carrier powder.
[0043] S3: adding manganese-modified titanium dioxide carrier powder to deionized water and continuously stirring to form a uniform turbid liquid, wherein the manganese-modified titanium dioxide carrier powder content is 11wt.%; adding polyvinyl pyrrolidone to the uniform turbid liquid according to the molar ratio of polyvinyl pyrrolidone, hexamethylenetetramine, ethylene glycol, and metal ions being 42:102:50:1, stirring until completely dissolved, then adding chromium nitrate and indium nitrate, stirring until completely dissolved, and finally adding hexamethylenetetramine and ethylene glycol, stirring continuously for 6 hours in a 75°C water bath environment until the mixed turbid liquid changes color;
[0044] S4 The mixed turbid liquid after discoloration was further evaporated and dehydrated in a 75℃ water bath environment to obtain a gel, which was then dried in air at 90℃ for 10h and then transferred to a muffle furnace for calcination at 550℃ for 5h with a heating rate of 5.5℃ / min; after cooling naturally to room temperature, it was taken out to obtain CrIn / Mn-TiO 2 DeNOx catalyst, the obtained deNOx catalyst has a manganese content of 4.5wt.%, a chromium content of 0.95wt.%, and an indium content of 1.8wt.%.
[0045] Comparative Example 1
[0046] Comparative Example 1 Preparation of manganese-modified titanium dioxide denitration catalyst (Mn-TiO 2 ), the difference between its preparation method and Example 1 is that: Steps S3 and S4 are not performed, and the final prepared Mn-TiO 2 The manganese content in the denitration catalyst is 4 wt.%.
[0047] Comparative Example 2
[0048] Comparative Example 2 Preparation of non-manganese-modified chromium-indium-based composite oxide denitrification catalyst (CrIn / TiO 2 ), the difference between its preparation method and that of Example 1 is that anatase-type titanium dioxide powder is used to replace the manganese-modified titanium dioxide carrier powder prepared in step S2 of Example 1, and the CrIn / TiO 2 The denitration catalyst has a chromium content of 1 wt. % and an indium content of 2 wt. %.
[0049] Comparative Example 3
[0050] Comparative Example 3 Preparation of manganese-modified chromium-based composite oxide denitrification catalyst (Cr / Mn-TiO 2 ), the difference between its preparation method and Example 1 is that: in step S3, no indium nitrate is added, and the Cr / Mn-TiO 2 The denitration catalyst has a manganese content of 4 wt.% and a chromium content of 1 wt.%.
[0051] Comparative Example 4
[0052] Comparative Example 4 Preparation of manganese-modified indium-based composite oxide denitrification catalyst (In / Mn-TiO 2 ), the difference between the preparation method and Example 1 is that in step S3, no chromium nitrate is added, and the final prepared In / Mn-TiO 2 The denitration catalyst has a manganese content of 4 wt.%, and an indium content of 2 wt.%.
[0053] Comparative Example 5
[0054] Comparative Example 5 Preparation of a conventional commercial vanadium-tungsten-titanium denitration catalyst (V 2 O 5 -WO 3 / TiO 2 ), the preparation method thereof comprises the following steps:
[0055] S1: ammonium metavanadate and oxalic acid are added to deionized water in a molar ratio of 1:3, and ultrasonic stirring is performed for 20 minutes to form a mixed solution. Ammonium metatungstate is added to the mixed solution (the molar ratio of ammonium metavanadate to ammonium metatungstate is 1:5), and stirring is continued for 30 minutes to fully dissolve, thereby forming solution A;
[0056] S2: Solution A was mixed with anatase titanium dioxide powder and stirred for 1 h, then stirred in a water bath at 80 °C until dry, and then transferred to a drying oven at 110 °C in a fume hood and dried for 12 h;
[0057] S3 The dried solid was ground into powder and placed in a muffle furnace, heated at a heating rate of 10°C / min, and calcined at 600°C for 5h. 2 O 5 -WO 3 / TiO 2 The denitration catalyst has a vanadium content of 1 wt. % and a tungsten content of 5 wt. %.
[0058] Comparative Example 6
[0059] Comparative Example 6 Preparation of Cobalt-Nickel-Based Composite Oxide Denitration Catalyst (CoNi / Mn-TiO 2 ), the difference between its preparation method and that of Example 1 is that cobalt nitrate and nickel nitrate are used to replace chromium nitrate and indium nitrate in step S3 of Example 1, and the CoNi / Mn-TiO 2 The denitration catalyst has a manganese content of 4 wt.%, a cobalt content of 1 wt.%, and a nickel content of 2 wt.%.
[0060] Comparative Example 7
[0061] Comparative Example 7 Preparation of chromium-cobalt based composite oxide denitration catalyst (CrCo / Mn-TiO 2 ), the difference between its preparation method and that of Example 1 is that cobalt nitrate is used to replace indium nitrate in step S3 of Example 1, and the CrCo / Mn-TiO 2 In the denitration catalyst, the manganese content is 4wt.%, the Cr content is 1wt.%, and the Co content is 2wt.%.
[0062] Comparative Example 8
[0063] Comparative Example 8 Preparation of Nickel-Indium-Based Composite Oxide Denitration Catalyst (NiIn / Mn-TiO 2 ), the difference between its preparation method and that of Example 1 is that nickel nitrate is used to replace the chromium nitrate in step S3 of Example 1, and the NiIn / Mn-TiO 2 In the denitration catalyst, the manganese content is 4wt.%, the Ni content is 1wt.%, and the In content is 2wt.%.
[0064] Experimental Example 1
[0065] In this experiment, HCl was used to prepare a chromium-indium-based composite oxide denitrification catalyst (CrIn / Mn-TiO 2 (Cl)), the preparation method thereof comprises the following steps:
[0066] S1 The CrIn / Mn-TiO prepared in Example 1 2 200 mg of denitration catalyst, in 100 ppm HCl, N 2 The treatment was carried out for 4 h under a balanced gas atmosphere with a total flow rate of 200 mL / min and a treatment temperature of 200 °C;
[0067] S2 HCl treated CrIn / Mn-TiO 2 The denitration catalyst was purged with nitrogen for 30 min at room temperature to obtain CrIn / Mn-TiO 2 (Cl) Denitrification catalyst.
[0068] Experimental Example 2
[0069] In this experiment, HCl was used to prepare a manganese-modified titanium dioxide denitrification catalyst (Mn-TiO 2 (Cl)), the preparation method thereof comprises the following steps:
[0070] S1: Mn-TiO prepared in Comparative Example 1 2 200mg of denitration catalyst in 100ppm HCl, N 2 The treatment was carried out for 4 h under a balanced gas atmosphere with a total flow rate of 200 mL / min and a treatment temperature of 200 °C;
[0071] S2 Mn-TiO treated with HCl 2 The denitration catalyst was purged with nitrogen for 30 min at room temperature to obtain Mn-TiO 2 (Cl) Denitrification catalyst.
[0072] The denitration catalysts prepared in Examples 1-3, Comparative Examples 1-8 and Experimental Examples 1-2 were tested for activity evaluation. The test conditions were: 500 ppm NO x (450ppm NO, 50ppm NO 2 ), 500ppm NH 3 , 4% O 2 , N 2 The total flow rate is 200 mL / min and the gas hourly space velocity (GHSV) is 40000 mL·g -1 ·h -1 .
[0073] like Figure 1 As shown in the figure, the denitration activity of the denitration catalysts of Examples 1-3 improves with the increase of aging time, and the improvement effect is not obvious after the aging time exceeds 23h, because the particles have formed a mature grid structure after Ostwald aging and accumulation. Figure 2As shown, the low-temperature denitration activity of Example 1 is higher than that of the denitration catalysts of Comparative Examples 2-5, which is attributed to the chromium and indium species forming Cr-OH and In-OH acid centers, which synergize with the manganese oxide oxidation center to promote the efficient acid cycle and redox cycle, and reduce the reaction energy barrier of the SCR reaction. Figure 3 As shown, compared with Comparative Examples 6-8, the temperature (T 50 ) and the temperature corresponding to 90% conversion rate (T 90 ) is significantly reduced, indicating that there is a better synergistic ability between chromium and indium; while the denitration catalysts of Comparative Examples 6-8 replace chromium and indium, resulting in partial destruction of the double acid center, which is not conducive to the reaction with SCR. Figure 4 As shown in the figure, the evaluation results of the adaptability of experimental examples 1-2 to resist HCl poisoning show that the denitration catalyst prepared in Example 1 has stronger resistance to HCl poisoning and can still achieve a denitration efficiency of more than 95% at 175°C. This is because the Bronsted acid sites provided by chromium and indium species can provide hydrogen protons, inhibiting HCl from combining with surface metal ions to form chloride salts after adsorption and causing deep poisoning and inactivation, thereby enhancing the ability of the denitration catalyst to resist HCl poisoning.
Claims
1. A method for preparing a low-temperature, high-efficiency, and highly adaptable chromium-indium-based composite oxide denitrification catalyst, characterized in that: The following steps are involved: S1: adding tetrabutyl titanate to anhydrous ethanol and mixing, and continuously stirring to form solution A; Mixing the manganese nitrate solution with anhydrous ethanol to form solution B; dropping solution B into solution A, stirring continuously to form a gel, and placing at room temperature for aging; S2 drying the aged gel and then calcining it, and taking it out after naturally cooling to room temperature to obtain a manganese-modified titanium dioxide carrier powder; S3: adding manganese-modified titanium dioxide carrier powder into water, stirring continuously to form a uniform turbid liquid, adding polyvinyl pyrrolidone, stirring until completely dissolved, adding chromium nitrate and indium nitrate in sequence, stirring until completely dissolved, then adding hexamethylenetetramine and ethylene glycol, stirring continuously in a water bath heating environment until the mixed turbid liquid changes color; S4: further evaporate and dehydrate the mixed turbid liquid after discoloration to obtain a gel, dry the gel and then calcine it, and then take it out after naturally cooling to room temperature to obtain a chromium-indium-based composite oxide denitrification catalyst.
2. The method for preparing the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst according to claim 1, characterized in that: In step S1, the concentration of manganese nitrate solution is 50-55wt.%, the volume ratio of tetrabutyl titanate to anhydrous ethanol is (0.5-0.6):1, the volume ratio of manganese nitrate solution to anhydrous ethanol is (0.2-0.4):1, the second continuous stirring time is 3-5h, and the aging time is 22-24h.
3. The method for preparing the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst according to claim 1, characterized in that: In step S2, the gel drying temperature is 70-80°C, and the drying time is 10-12h; during calcination, the heating rate is 4.5-5.5°C / min, the calcination temperature is 450-500°C, and the calcination time is 4-5h.
4. The method for preparing the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst according to claim 1, characterized in that: In step S3, the content of manganese-modified titanium dioxide carrier powder in the uniform turbid liquid is 10-11wt.%, the water bath heating temperature is 75-80°C, the molar ratio of polyvinyl pyrrolidone, hexamethylenetetramine, ethylene glycol, and chromium and indium nitrates is (40-42):(98-102):(48-50):1; and the stirring time of the final mixed turbid liquid is 5-6h.
5. The method for preparing the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst according to claim 1, characterized in that: In step S4, the evaporation and dehydration temperature is 75-80°C.
6. The method for preparing the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst according to claim 1, characterized in that: In step S4, the gel drying temperature is 90-100°C, and the drying time is 10-12h; during calcination, the heating rate is 4.5-5.5°C / min, the calcination temperature is 550-600°C, and the calcination time is 4-5h.
7. The method for preparing the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst according to claim 1, characterized in that: The chromium-indium-based composite oxide denitration catalyst has a manganese content of 4-4.5 wt.%, a chromium content of 0.9-1 wt.%, and an indium content of 1.8-2 wt.%.
8. A low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst prepared by the method for preparing a low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitration catalyst as described in any one of claims 1 to 7.
9. The use of the low-temperature, high-efficiency, high-adaptability chromium-indium-based composite oxide denitrification catalyst as claimed in claim 8, characterized in that: The low-temperature, high-efficiency and high-adaptability chromium-indium-based composite oxide denitrification catalyst removes NO x When, the reaction temperature is 150-325°C.
Citation Information
Patent Citations
Manganese-based low-temperature denitration catalyst taking TiO2-SiO2 as carrier and preparation method thereof
CN103240081A
Low temperature denitration catalytic addictive and preparation method thereof
CN103537279A
Chromium tungsten zirconium composite oxide denitration catalyst as well as preparation method and application thereof
CN106140142A
Phosphotungstic acid modified nano iron oxide SCR denitration catalyst as well as preparation method and application thereof
CN111250120A
Preparation method of powerful water-resistant and sulfur-resistant denitration catalyst
CN114308052A